Empathy skill among a sample of psychological support workers in Lattakia province in light of some variables - الشريف , ليلى; محفوض, مروة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aimed to study the level of empathy skills among psychological support workers in Lattakia province and to test the differences in empathy skills in the light of variables: gender, years of experience and nature of work (paid/voluntary). A sample of (80) psychological support workers was assigned randomly from paid community centers and non-profit voluntary organizations. The empathy scale prepared by Jifferson (2012) and translated by the researcher was used, after verifying its psychometric characteristics. The researcher followed the descriptive analytical curriculum. The results indicated that there is a high level of empathy skills among psychological support workers, and statistically significant differences in empathy skills among psychological support workers according to study variables (gender for females, years of experience for the less experienced, and nature of work for voluntary).